THE OPEN SCIENCE PLATFORM AND APPLICATION OF ITS COMPONENTS IN THE EDUCATIONAL PROCESS - Marienko Майя; Shyshkina Марія (Journal of Information Technologies in Education (ITE), 2021)
The article considers the concept of open science and open data in the context of educational applications. As the Roadmap for Ukraine’s integration into the European Research Area was approved in 2018, some steps have already been taken to use the ideas of open science. In some educational establishments, the learning content includes issues and topics related to open data or open science. The current state of the art and the experience of using open science systems in educational process in Ukraine is undertaken. Such experience will contribute to the further creation and development of a national scientific infrastructure, for the promotion and providing free access to any state-funded research. However, the analysis showed that currently there is lack of methods (or methodological systems) of using open science services to train educators and teachers in particular for work in scientific lyceums. A survey of educators "Using open science services to pose and resolve the research problem" was conducted, which showed that most respondents are primarily interested in the materials of their colleagues from professional journals mainly not widely accessed. Only a quarter of respondents know what open science is. It has been found that open access services (including scientific materials) are tools for using the ideas of open science. As an example, the open access service arXiv is considered: the basics of working with this service and the features of its use are described. Services for collaborative work on educational projects can also be considered as open science services, as most of them have the tools for further, public disclosure of the results. An example is the review of Discord Messenger, which recently claims to be used in cloud-based systems, contains tools that are cloud-based and easily integrated with other services (or systems) through open source. In addition, there are tools available to create open communities (servers) for further connection of any user. The European Open Science Cloud (EOSC) deserves special attention, as it is a rather powerful platform for the use both by scientists and educators. The advisable ways of application of its components in the educational process are outlined.